Doing Age in a Digitized World—A Material Praxeology of Aging With Technology - Wanka, Anna; Gallistl, Vera (Frontiers in Sociology, 2018)
Digital technologies have gained vast relevance in postmodern societies and digital infrastructures are substantially integrated into the everyday lives of older people. This digitization is reframing the norms and practices of later life as well as the social construct of age itself. Despite the increasing amount of studies in the field of aging and technologies, it still lacks theorizing. This paper addresses this deficit, suggesting that the study of aging and technologies could profit from a comprehensive integration of theories from the sociology of aging, critical gerontology and science-and-technology studies. We aim to make a theoretical contribution to this issue, asking: How is age being done in a digitized world? Applying a praxeological approach to aging and technologies, we firstly examine how theoretical and empirical work has constructed aging with technologies so far and identify its shortcomings. Some of this work so far lacks a proper consideration of social inequalities within these processes, whereas other studies lack a thorough consideration of materialities. Secondly, in an attempt to equally ‘praxeologize’ and ‘materialize’ the study of aging and technologies we develop a theoretical model that aims to overcome these shortcomings. In what we frame as a material praxeology of aging with technology, we are concerned with how age is being done through discursive formations, set into practice through social and material practices and involved in the (re)production of social inequalities. Enriching a Bordieuan terminology of social fields with notions of non-human agency, this praxeology is founded on three assumptions: 1) Social fields constitute the contexts in which age as a social phenomenon is being done with and through technologies 2) Human and non-human agents are equally involved in this process 3) The actions of the involved agents emerge from an agency distributed among them, and are structured through the power relations between them. Thirdly, we exemplify the application of this model by reference to a research project in the field of Active and Assistive Living.